Discrete fracture network based approaches to assessing inter-ramp design - Valerio, M; Rogers, S; Lawrence, KP; Moffitt, KM; Rysdahl, B; Gaida, M (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
At the inter-ramp scale, critical failure mechanisms in slopes consisting of moderately to highly fractured competent rock masses commonly involve a combination of failure along discontinuities and through the rock mass. While several analysis methods are available for assessing inter-ramp slope stability (such as kinematic, limit equilibrium, and elastic/plastic modelling), most have limitations when applied to failure mechanisms involving structure and rock mass. For example, simple kinematic methods are effective for assessing structurally controlled failure mechanisms, but at the inter-ramp scale, more sophisticated approaches are required to evaluate potential step-path failures that involve shearing through a combination of structure and rock mass. For inter-ramp stability analyses where failure through rock mass is expected, limit equilibrium methods and continuum stress-displacement modelling (e.g. finite element and finite difference tools) are commonly used. Structural sets that provide preferential planes of weakness within the rock mass can be incorporated into these types of analyses as ubiquitous joints or anisotropic strength orientations. However, these modelling techniques are not practical for evaluating variations in orientation, spacing, and persistence of several structural sets or for evaluating the impact of multiple structural sets in three dimensions. This paper presents alternative approaches for inter-ramp slope stability analysis and design using discrete fracture network (DFN) based methods. DFN models provide synthetic realisations of fracture networks within pit walls that can be used to: 1) estimate rock mass bridges using search algorithms that identify failure pathways of least resistance through networks with unconstrained fracture orientation, spacing, or length variations; and 2) identify fully formed or nearly fully formed three-dimensional (3D) rock blocks and evaluate their stability. This paper describes a method for rock mass bridge characterisation using stochastic DFNs and how this can be incorporated into kinematic inter-ramp stability analyses by adjusting discontinuity strengths. This paper also describes how the stability of rock blocks identified in DFN models can be assessed using a custom 3D stress-based limit equilibrium tool that can approximate composite structural and rock mass block boundaries. A case study is presented to illustrate how these DFN-based approaches were applied to develop inter-ramp slope angle recommendations for a pushback design at the Bingham Canyon mine. The analysis methods described in this paper provide practical tools for efficiently evaluating complex failure mechanisms and informing the choice of design inter-ramp angles.
Keywords: inter-ramp slope stability; DFN; rock mass bridges; kinematic analysis; 3D limit equilibrium